Sealing Ability of the Formed Apical Calcified Bridge in Open Apex Roots (Mustansiria Dental Journal, 2018)
A successful endodontic treatment requires that the apex of the treated tooth becompletely and densely sealed with root canal filling material. One of the mostdifficult endodontic problems is the management of necrotic immature tooth due tothe blunderbuss apex and the difficulty in achieving a tight seal between the root canalsystem and the external surface of the tooth. The aim of this study was to evaluate thesealing ability the apical calcified bridge formed by calcium hydroxide paste, whiteMTA or gray MTA during apexification procedure.Thirty premolars with single root canals were prepared to simulate an open apex.These roots were divided into 3 groups as follow: Group A: 10 roots filled withCa(OH)2 paste, Group B: 10 roots filled with white MTA, and Group C: 10 rootsfilled with gray MTA. Each root was placed in a polyethylene vial containing 25 m1of synthetic tissue fluid (STF) and incubated at 37°C for 3 months. After 3 monthsand the formation of calcified bridge, each root was immersed in 2% freshly preparedMethylene blue dye in 5 ml plastic vial for seven days. After the leakage period, theroots were removed from the dye and the leakage in all roots was examined bymeasuring the linear extent of dye penetration from the apical end of the canalpreparation to the coronal direction by means of a light stereomicroscope at (40 X)magnification with calibrated grid.Ca(OH)2 paste group has the highest mean value of apical dye penetrationfollowed by WMTA, while GMTA group shows the lowest mean value of apical dyepenetration. There was a highly significant difference in the apical dye penetration(p